2020
DOI: 10.3390/antiox9080729
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Protects Retinal Photoreceptor Cells against High Glucose-Induced Oxidative Stress by Induction of Antioxidant Enzymes via the PI3K/Akt/Nrf2 Pathway

Abstract: Diabetic retinopathy (DR) is a major microvascular complication that can lead to severe visual impairment in patients with diabetes. The elevated oxidative stress and increased reactive oxygen species (ROS) production induced by hyperglycemia have been reported to play an important role in the complex pathogenesis of DR. Astaxanthin (AST), a natural carotenoid derivative, has been recently recognized as a strong free radical scavenger and might, therefore, be beneficial in different diseases, including DR. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…In particular, rod OS appear vulnerable to oxidative stress [ 8 , 17 , 41 , 42 ], which drives the retinal degeneration [ 17 , 18 ]. On the other hand, antioxidants were shown to mitigate signs of DR in animal diabetic models [ 43 ] and in cultured photoreceptor cells (661W) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rod OS appear vulnerable to oxidative stress [ 8 , 17 , 41 , 42 ], which drives the retinal degeneration [ 17 , 18 ]. On the other hand, antioxidants were shown to mitigate signs of DR in animal diabetic models [ 43 ] and in cultured photoreceptor cells (661W) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Repeated cell exposure to oxidative stress leads to the insufficient activity of cellular antioxidant enzymes responding to ROS, contributing to the inability of RPE cells to prevent the consequent damages. 31 Excess intracellular ROS brings about the damage of macromolecules and acts as cellular messengers to activate a cascade of biochemical and molecular events and disrupt the normal mechanisms of cellular signaling, which leads to the disruption of normal retinal cellular physiology and apoptosis. 12 , 13 Therefore, anti-oxidation and anti-apoptosis may represent a promising therapy for the treatment of DR. DHM, also known as ampelopsin, is a dihydroflavonol flavonoid that is found in ampelopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of Nrf2 may alleviate oxidative stress injury in PIPN (Singh et al, 2019) [29]. Notably, increasing evidence has suggested that PI3K/Akt is upstream of Nrf2 [30,31]. Nrf2-mediated gene expression correlates with the activation of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%